探究團隊覺知訊息對合作學習的效益 - 林哲立(Che-Li Lin) (Jiao yu yu xin li yan jiu, 2024)
Collaborative learning has both educational meaning and challenges. Group awareness can promote metacognitive mechanisms for an individual and a group, but more empirical research is needed. This study aims to investigate the effects of group awareness information on individual and team performance. A quasi-experimental design was adopted, with the experimental group incorporating two types of group awareness, while the control group consisted of traditional small group discussion. In the experimental group, social group awareness and cognitive group awareness were integrated into the instructional activities. Cognitive group awareness was implemented through collaborative annotations and shared concept maps. Social group awareness was implemented through an Interactive Response System, which all students responded their learning engagement and emotions, which were then fed back to the classmates. The subjects of the study were university students taking “Freshman English” in northern Taiwan. The experimental